Implementasi Kebijakan Operator Per Jenjang Atau Kecamatan Seksi Pais Kantor Kementerian Agama Kabupaten Sidoarjo Dalam Mengelola Guru PAI Se-Kabupaten Sidoarjo - Muh. Khoirul Rifa’i; Nurhana Fakhriyah Imtinan; Kurnia Dewi, Febriana (Proceedings of Annual Conference on Islamic Educational Management, 2022)
Operator policy per level or sub-district aims to improve service quality, and GPAI data owned by the Office of the Ministry of Religion of Sidoarjo Regency. The study used descriptive qualitative methods with triangulation data collection techniques and data analysis using Miles and Huberman theory. The policy was taken in 2019 and carried out the first task of tracing GPAI activity data throughout Sidoarjo Regency, then carrying out routine activities of updating EMIS and GPAI SIAGA data throughout Sidoarjo Regency. The result of this policy is that there are around 60 operators per level or sub-district at various levels from kindergarten to high school/vocational school, GPAI data has been neatly and accurately arranged, professional allowances can be received faster than usual, and the active SIAGA account reaches 90%.